FOUR NEW TAXA OF ASTERACEAE IN SUMATRA - Sri Sudarmiyati Tjitrosoedirjo (REINWARDTIA, 2002)
TJITROSOEDIRDJO, SRI S. 2002. Four new taxa of Asteraceae in Sumatra. Reinwardtia 12(1): 125–128. ? Four new taxa of Asteraceae in Sumatra are described: Prenanthes L. (2 species), Senecio L. (1 species) and Emilia sonchifolia (L.) DC. (1 variety).